An Investigation of Dynamic Soil-Structure Interaction on the Seismic Behavior of RC Base-Isolated Buildings - Santoso, Alvin K.; Saito, Taiki (Salehan Institute of Higher Education, 2024)
Soil-structure interaction (SSI) can significantly influence earthquake responses in base-isolated (BI) buildings, yet it is often overlooked in practice due to the high computational demands of complex analyses. This study investigates SSI effects on reinforced concrete (RC) base-isolated buildings, idealizing SSI with a cone model. Three BI building models of varying heights and soil characteristics were analyzed using modal and nonlinear time history analysis. The base isolation system incorporated elastic sliding bearings, lead rubber bearings, natural rubber bearings, and oil dampers. The SSI model was idealized considering hard, medium, and soft soils. To simulate earthquake input, three artificial ground motions with different phase characteristics were generated to match the design response spectrum according to the Japanese code. The seismic responses of the base-isolated building models with SSI were compared to those of models without SSI. Modal analysis showed that the natural period increased with softer soil profiles. In the first and second modes, the natural period lengthened as the building’s aspect ratio increased. Conversely, in the higher modes with a rocking pattern, the building with the lowest aspect ratio exhibited the longest natural period. Overall, implementing SSI generally reduced seismic responses, notably lowering story drift, acceleration, and force, particularly for buildings on soft soil. However, the SSI effect significantly increased the base rotation angle in high aspect ratio buildings on soft and medium soils. These findings indicate that including SSI in analysis is essential for more realistic seismic response predictions, especially for tall, slender base-isolated buildings. Doi: 10.28991/CEJ-2024-010-11-01 Full Text: PDF